2022
DOI: 10.1136/jitc-2021-004001
|View full text |Cite
|
Sign up to set email alerts
|

Ascites and resistance to immune checkpoint inhibition in dMMR/MSI-H metastatic colorectal and gastric cancers

Abstract: BackgroundDespite unprecedented benefit from immune checkpoint inhibitors (ICIs) in patients with mismatch repair deficient (dMMR)/microsatellite instability high (MSI-H) advanced gastrointestinal cancers, a relevant proportion of patients shows primary resistance or short-term disease control. Since malignant effusions represent an immune-suppressed niche, we investigated whether peritoneal involvement with or without ascites is a poor prognostic factor in patients with dMMR/MSI-H metastatic colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“… 396 , 397 In May 2017, pembrolizumab was approved for solid tumor patients with MSI-H or dMMR who have progressed after previous treatment and have no satisfactory alternative treatment. 386 , 396 , 398 In 2017 and 2018, the FDA successively approved the treatment of metastatic colorectal cancer patients with MSI-H or dMMR after treatment with fluorouracil, oxaliplatin and nivolumab alone or in combination with ipilimumab. Therefore, MSI-H and dMMR can be used as primary screening methods.…”
Section: Biomarkers For Immunotherapy—lessons From Icb and Car-t Cellsmentioning
confidence: 99%
“… 396 , 397 In May 2017, pembrolizumab was approved for solid tumor patients with MSI-H or dMMR who have progressed after previous treatment and have no satisfactory alternative treatment. 386 , 396 , 398 In 2017 and 2018, the FDA successively approved the treatment of metastatic colorectal cancer patients with MSI-H or dMMR after treatment with fluorouracil, oxaliplatin and nivolumab alone or in combination with ipilimumab. Therefore, MSI-H and dMMR can be used as primary screening methods.…”
Section: Biomarkers For Immunotherapy—lessons From Icb and Car-t Cellsmentioning
confidence: 99%
“…We tended to ascribe the results to the small sample size-driven instability of the analysis model. Actually, it was reported that patients with peritoneal metastases and ascites had worse PFS and OS than those without peritoneal metastases and those with peritoneal metastases and no ascites when receiving ICI-based therapy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fucà et al showed that the presence of peritoneal metastases and ascites was associated to a poor outcome in a cohort of 502 patients with dMMR/MSI-H mCRC treated with ICI [ 44 ]. This has been hypothesized to be a consequence of an immune-suppressive environment in serous cavities.…”
Section: Resistance To Icis In Dmmr/msi-h Mcrc Patientsmentioning
confidence: 99%